2021
DOI: 10.1021/acsami.1c18392
|View full text |Cite
|
Sign up to set email alerts
|

Controllable Circularly Polarized Electroluminescence Performance Improved by the Dihedral Angle of Chiral-Bridged Binaphthyl-Type Dopant Inducers

Abstract: Chirality of 1,1′-binaphthol (BINOL) is due to the restricted rotation between two naphthalene rings, and its skeletal structure of binaphthyl unit can be further modified by choosing functionalized substituents to afford the enlarged chiral induction effect. In this paper, we designed and synthesized nine chiral binaphthyl derivatives ( R/S-1–R/S-9) as circularly polarized electroluminescence (CP-EL) inducers by inserting various bridged alkyl chains into the hydroxyl groups of BINOL or introducing functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 42 publications
1
23
0
Order By: Relevance
“…The exchange of (−)-CPEE and (+)-CPEE was closely related to the inversion of excimer chirality caused by the presence or absence of intermolecular hydrogen bonds in the excited state. Our group recently carried out a series of experiments on the amplified CPL emission promoted by the intermolecular chiral transfer of chiral binaphthyl inducers with the anchored dihedral angle 9 , 10 , 40 42 . In this paper, we found a dynamically stable and amplified CPEE of an achiral Py-based dye regulated through the solvation effect of chiral co-assembly process.…”
Section: Introductionmentioning
confidence: 99%
“…The exchange of (−)-CPEE and (+)-CPEE was closely related to the inversion of excimer chirality caused by the presence or absence of intermolecular hydrogen bonds in the excited state. Our group recently carried out a series of experiments on the amplified CPL emission promoted by the intermolecular chiral transfer of chiral binaphthyl inducers with the anchored dihedral angle 9 , 10 , 40 42 . In this paper, we found a dynamically stable and amplified CPEE of an achiral Py-based dye regulated through the solvation effect of chiral co-assembly process.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to cyano-carbazole-type TADF enantiomers, Cheng et al reported a new pair of chiral TADF molecules R / S - BDTPA with BINOL as the chiral perturbed unit, biphenyl boron β-diketonate as an electron acceptor, and biphenylamine as an electron donor in 2021. 22 The obtained chiral boron complexes displayed obvious CPL activities with | g lum | values of 2.2 × 10 −3 and red delayed fluorescence of about 600 nm. Impressively, solution-processed CP-OLEDs with the chiral TADF emitters displayed red CPEL ( λ EL = 600 nm) with | g EL | values of 2.6 × 10 −3 and EQE max of 2.0%.…”
Section: Chiral Tadf Molecules Based On a Chiral Perturbation Strategymentioning
confidence: 96%
“…To realize it, one of the most effective methods is doping chiral luminogens into achiral nematic liquid crystals (N-LCs). Besides g lum , another important parameter of CPL is the polarization direction (left-handed and right-handed). Inversion of CPL signals was usually realized by changing the molecular structure or chirality of chiral dopants. It would be more convenient to inverse the CPL signals of N*-LC by simply adjusting the doping ratio of chiral dopants; however, related LC systems were rarely reported.…”
Section: Introductionmentioning
confidence: 99%